PENYELESAIAN SENGKETA PERBANKAN SYARIAH SESUAI ISI AKAD BERDASARKAN KETENTUAN UNDANG-UNDANG NOMOR 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 93/PUU-X/2012 - Purnama Hidayat Harahap; Bismar Nasution; Hasballah Thaib; Utary Maharani Barus (Universitas Sumatera Utara, 2016)
ABSTRAK The research showed that the sharia banking still used the Law by District Court as an alternative of the settlement for the Sharia banking disputes because the legal counseling about the forum of settlement for the sharia banking disputes was not effective yet as stipulated in Article 55 Paragraph (1) of the Law No. 21/ 2008 regarding Sharia Banking in conjunction to Article 49 of the Law No. 3/ 2006 regarding the Religious Jurisdiction which states that it assertively gives the absolute authority to the Religious Jurisdiction to receive and settle the sharia economic disputes including the sharia banking disputes; there is a factor of the readiness of the Religious Jurisdiction to settle the sharia banking disputes;the next factor was that the judge of the District Court did not refuse the lawsuit addressed to him even though it was obvious that the absolute authority is possessed by the Religious Jurisdiction; another factor was that there was lack of trust from the customers of sharia banks to the Religious Jurisdiction; because the Religious Jurisdiction was so far considered to only settle the divorce cases. Furthermore, the results also showed that the judge viewed that these provisions are contrary to Article 28D Paragraph (1) of the 1945 Constitution explaining that every person shall have the right of recognition, guarantees, protection and certainty before a just law, and of equal treatment before the law. The settlement for the sharia banking disputes in accordance with the contract contents after the Constitutional Court Verdict No. 93/PUU-X/2012 tend to have changed the clausal forum for the dispute settlement, which previously referred to the District Court, now it refers to the Religious Jurisdiction and Basyarnas (National Sharia Arbitration Agency). It can be seen in the contracts made at some Sharia Banks in Indonesia, such as Bank Syariah Mandiri, Bank BRI Syariah, Bank Muamalat Syariah, Bank Sumut Syariah, and Bank BTN Syariah. Keywords: Settlement for Sharia Banking Dispute, Contract Contents, Constitutional Court Verdict